Analisis SWOT Produktivitas Karet di Kelurahan Pangkalan Balai Kabupaten Banyuasin - Rosita Rosita; Rismarini Rismarini (Jurnal Manajemen Bisnis Digital Terkini, 2025)
Rubber productivity is very important for the life and welfare of rubber farmers in Pangkalan Balai Sub-district, Banyuasin, where most of the population is rubber farmers. In this study, SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis was used to analyze the influence of the internal and external environment of rubber farmers that affect the strategies used to increase rubber productivity in Pangkalan Balai Sub-district. This study used a descriptive-qualitative method by conducting interviews with 10 rubber farmers spread across Pangkalan Balai Sub-district. The results of this study are known based on IFAS and EFAS and the SWOT matrix is ​​in quadrant III, namely using a defensive strategy. The implications of this study are used to increase rubber productivity in Pangkalan Balai Sub-district, namely by synergizing with the local government with a defensive strategy.